Idiopathic functional urinary outflow tract obstruction in dogs, a retrospective case series (2010‐2021): 31 cases - Kathrina Mathews; Christine Toedebusch; Carrie Palm; Allison Kendall; Jodi L. Westropp (Journal of Veterinary Internal Medicine, 2023)
Abstract Background Idiopathic functional urinary outflow tract obstruction (iFUOTO) is an uncommon but life‐limiting disease whose etiology and clinical course of disease remain poorly understood. Objective Characterize signalment, clinical signs, clinicopathologic findings, treatments, and propose a standardized response score for dogs with iFUOTO. Animals Thirty‐one client‐owned dogs diagnosed with iFUOTO. Methods Retrospective case series. Medical records from 2010 to 2021 were reviewed and findings recorded. Dogs were categorized based on the presence or absence of overt signs of neurological disease. Response to treatment was scored. Results Thirty‐one dogs were included. All dogs had stranguria and 14 (45%) had overflow urinary incontinence. Mean age of onset for signs was 6.9 years±8 months. Twenty‐four dogs (77%) were castrated males, 5 (16%) intact males, and 2 (6%) spayed females. Eight (26%) of dogs had overt neurological deficits. Follow‐up data were available for 29 dogs (median 38 days, range: 2‐1277). Final outcome scores were not significantly different among dogs with overt signs of neurological disease (median score 2.5; range: 0‐3) and those without (median score 1; range; 0‐3; P = .35). Treatments included alpha antagonists, skeletal muscle relaxants, parasympathomimetics, anti‐inflammatories, castration, temporary placement of a urethral catheter, or a combination of these. Conclusions and Clinical Relevance Multimodal treatment was frequently prescribed, but a standard outcome score is needed to evaluate the effectiveness of these therapies. Serial neurological examinations and monitoring of the dogs' dysuria are warranted.